Improvement of migraine headaches after percutaneous closure of patent foramen ovale for secondary prevention of paradoxical embolism. Issue 12 (10th June 2010) - Wahl, Andreas; Praz, Fabien; Tai, Tony; Findling, Oliver; Walpoth, Nazan; Nedeltchev, Krassen; Schwerzmann, Markus; Windecker, Stephan; Mattle, Heinrich P; Meier, Bernhard
Abstract : Objectives: Patent foramen ovale (PFO) has been linked to migraine, and an improvement in migraine prevalence or frequency has been reported after PFO closure for other reasons. We sought to identify whether there is a specific patient population of migraineurs which may be more susceptible to benefiting from PFO closure. Design: Retrospective cohort study. Setting: Tertiary care centre. Participants: 603 consecutive patients undergoing percutaneous PFO closure for secondary prevention of paradoxical embolism. Interventions: PFO closure using the Amplatzer PFO occluder. Main outcome measures: Improvement of migraine symptoms. Results: 150 patients (25%; aged 51±11 years) suffered from migraine, including 96 patients with migraine with aura. All implantation procedures were successful, without procedural complications. Contrast transoesophageal echocardiography at 6 months showed complete PFO closure in 136 patients (91%), whereas a minimal, moderate or large residual shunt persisted in 11 (7%), 2 (1%) or 1 (1%) patients, respectively. During 5.0±1.9 years of follow-up, one TIA and one ischaemic stroke occurred. Migraine headaches disappeared in 51 patients (34%) and improved in 72 additional patients (48%). Mean subjective improvement was 69±35%. Overall, mean headache frequency (from 2−3×/month to 1×/month; p <0.001), duration (from 4–72 to <4 h; p <0.001) and intensity (from 7±2 to 3±3; p <0.001) improved significantly. The prevalence of any migraine headaches (from 100% to 66%; p <0.001), migraine with aura (from 64% to 19%; p <0.001) and the number of patients taking any migraine medication (from 90% to 50%; p <0.001) decreased significantly. Both the presence of aura (OR 3.2; 95%CI 1.3 to 8.2; p =0.014) and high pain intensity at baseline (pain scale >5; OR 3.3; 95%CI 1.3 to 8.4; p =0.013) were independent predictors of response to PFO closure. A residual shunt had no influence on migraine improvement (OR 0.6; 95%CI 0.1 to 2.3; p =0.42). Conclusions: These results suggest that percutaneous PFO closure durably alters the spontaneous course of shunt-associated migraine, especially but not exclusively in case of migraine with aura.